Students’ Perception of Canva and Its Impact on Presentation Performance in Higher Education - Hasibuan, Asriani; Hsb, Elysa Rohayani; Sinaga, Yusni (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This study investigates eighth-semester students’ perceptions of Canva use and its effect on presentation performance in the English Language Education Study Program at Institut Pendidikan Tapanuli Selatan. Twenty students were purposively sampled as research participants to represent those who had sufficient experience using digital presentation tools in academic contexts. Data were collected through close-ended questionnaires and classroom observations to obtain both perceptual and behavioral evidence regarding the use of Canva in presentations. Results from the questionnaire analysis reveal generally positive student perceptions of Canva as a helpful and user-friendly design tool for creating engaging presentation slides. Many students strongly agreed that Canva enhanced their creativity, visual design skills, and enjoyment during the presentation process, which in turn contributed significantly to improved confidence and delivery. In addition, students perceived Canva as an effective platform that helped them organize content more systematically and present ideas more clearly. Classroom observations corroborated these findings, showing enhanced student performance when Canva was utilized, particularly in terms of slide aesthetics, audience engagement, and presentation fluency. Overall, the findings indicate that integrating Canva into English language learning activities can positively support students’ presentation skills and foster a more engaging and interactive learning environment.Keywords : Canva Utilization, English Language Education, , Higher Education , Presentation Performance, Students’ Perception.